SOSIALISASI HAK PILIH PEMILIH PEMULA PADA SISWA SEKOLAH MENENGAH ATAS ST. LOUIS 2 DI SURABAYA UNTUK MENINGKATKAN JUMLAH PEMILIH PADA PEMILIHAN UMUM TAHUN 2024 - Nany Suryawati; Martika Dini Syahputri (Jurnal Abdimas Bina Bangsa, 2023)
Suffrage is a right that must be fulfilled and exercised, because it is the embodiment of democratic principles in a country that is sovereign of the people. General elections in Indonesia are held every 5 (five) years, therefore, every year there is an increase in the number of voters. Observing this, through the method of approach, to prepare novice voters to exercise their right to vote without hesitation, especially on novice voters, who have met the age requirements Because these novice voters do not understand the importance of their participation in the general election, and also there are several obstacles that become obstacles to the fulfillment of the right to vote, it is necessary to identify existing obstacles and prepare efforts to overcome obstacles aforementioned. One of the efforts that will be carried out by the Community Service Team, through persuasive legal approaches and social approaches, is by socializing the 1945 NRI Constitution along with an understanding of citizens' voting rights as a manifestation of democratic principles, at the democratic party, namely: General Elections. Understanding the Constitution and Human Rights of Citizens in the political field is a way to minimize the non-use of the right to vote, so that in the upcoming General Election, namely: in 2024, it is necessary to carry out an activity that supports the increase in voter turnout in the 2024 general election, especially in the novice voter group of students of St. Louis 2 High School Surabaya. This activity is a manifestation of people's sovereignty in the form of general elections, either directly or indirectly through people's representatives